Human-jaguars coexistence: social factors influencing jaguar conservation in Southern Bolivia - Caruso, F; Perovic, P; Talamo, A; Sillero-Zubiri, C; Altrichter, M (Noel Kempff Mercado Natural History Museum, 2022)
Jaguar (Panthera onca) populations are declining in Bolivia, due to anthropogenic threats. Understanding the attitudes and perceptions of local people toward threatened species, and the factors that can influence them, is crucial for their protection. This study evaluated how the level of knowledge, attitudes, and perceptions towards jaguars among local people in southern Bolivia varied depending on their level of education, age, and occupation. We interviewed 139 people who live in and around two protected areas. Positive perceptions and attitudes towards jaguars were associated with higher levels of formal education and with people's occupation. Negative attitudes and perceptions towards the species were determined by fear; people saw jaguars as a potential threat to their lives. Socioeconomic factors that affect the level of tolerance towards jaguars are not related only to economic losses. Our results can inform the design, orientation, execution, and evaluation of future species conservation projects in Bolivia.